O conhecimento cotidiano sobre qualidade de vida de idosos - Sarmento, Ana Margareth Marques Fonseca (2015)
Population aging is one of the greatest public health challenges. The aging process follows the evolution of humanity and highlights the health-disease in the elderly as a biopsychosocial phenomenon. The social value of the elderly policies arouse the interest of researchers from different areas in the theme regards quality of life in old age. However with increased survival there is a search for improving the quality of life in order to achieve a successful old age, respecting their values and beliefs, their vision of health and social action. The quality of life multidimensional and social representations, run from the main aspects to be considered in relation to life and health of the elderly. In this perspective the present study aims to understand the social representations of the elderly on the quality of life; measure the quality of life of older people; and analyze the relationship between quality of life and social representations of the elderly. This is a secondary database study, was used as the theoretical social representations with emphasis on structural approach. It involved 250 elderly of the service network SUS João Pessoa-PB. Was used as collection instruments, the questionnaire with demographic data, TALP and WHOQOL instruments for measuring quality of life. The data relating to TALP was processed by Evoc software and sociodemographic and instruments using statistical programs SPSS 13.0. The results are graphs tables, of the elderly studied the average age was between 60 and 79 years (85,2%), most of the female (70,4%), married or living with a partner (a), with a monthly income of less than one to three minimum wages (70,8%). Regarding the perception of the elderly quality of life most consider it good (52,0%) and (50,4%) says their satisfied with their health. The social representations based on structural approach, the central elements are the feed and assistance where for the elderly, there is concern about the feed and the importance of this in their health intervened thus the quality of life, as well as a quality care that enables them to be assisted in their needs. Older people still associate quality of life the presence of peace shown by the tranquility to have its own house representing for them a rest, plus the idea of their being surrounded by good friends and getting a lot of love with God above all things, and being careful enjoy good health and be able to work. Considering the issues raised is expected that these results can provide support for implementation of effective and preventive health education programs to a better quality of life turned for the elderly.